Esophageal perforation due to inadvertent swallowing of a dental prosthesis - Deniz TİHAN and Didem TRABULUS and Aykut ALTUNKAYA and Selami KARACA and Alper CİHAN and Halil ALIŞ (Turkish Journal of Gastroenterology, 2019)
-